University foreign language education in the context of the formation of a new teacher (Pedagogy of Higher and Secondary Education, 2013)
Pet’ko L. V. University foreign language education in the context of the formation of a new teacher.The author examines the modern approaches to the understanding and developing of foreign language education of future teachers in the university training.The article describes necessity of forming of a new teacher, who will be a modern personality, in the process of foreign language teaching in professional way of the students of higher educational establishments.
Keywords: professional pedagogy; university foreign language education; future teachers; foreign language in professional way